Situation Report: Romania, 24 June 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Verdet Addresses Comecon Council Session in Prague Investments Continue to Fall Short of Target Deficiencies in the supply and Maintenance of Consumer Goods Agriculture Reorganized Again